ANALISIS PERILAKU PENGGUNA ANGKUTAN UMUM TRANSPORTASI ANTARMODA - Y. I. Wicaksono; Joko Siswanto (Diponegoro University, 2014)
[Title: Analysis of User Behaviour for Public Transport Special for Intermodes Transportation]In traveling, each rider will choose the route that gives the minimum fare. The journey can be expressed in terms of monetary cost, travel time, distance, safety, comfort, and cost is not borne by the traveler (social cost). Attributes are specific to each road segment (link), so it can’t be aggregated for a more long. Attribute segment in transport modeling approach behavior (behavioral), including 2 primary system, the system of activity attributes and attribute the traveler service systems. Pretty much the traveler who wants to use mass transit intermodal transportation. This research was conducted in the city of Semarang Metropolitan Indonesia: identify the purpose and perception of public transport user behavior on the network and create a model for inter-user behavior on public transport intermodal network. The combined value of the coeffient of determination of the overall model is 0.931. This means that the model is able to explain 93.1% inter-user behaviour. Behavioural characteristic of users of public transport in the intermodal network in the form of the number of activities that a lot, have enough users mature age, education level is high enough, is not associated with gender, the limitations of private vehicle ownwership. Perception of public transport user behaviior on the network inter-linked with the comfort, safety, convenience, capacity, quality and quantity of good network, resonable travel expenses, as well as interdiciplinary operator.